Digital narratives for a changing world: An international virtual learning experience on climate change - Udoh, Isidore; Workman, Margaret (Journal of International Students, 2025)
As the climate crisis continues to accelerate, multiple sectors of society are working collaboratively to research, develop, and implement strategies and policies that target the sources of the problem to slow or reverse climate change impacts. As centers of innovation, institutions of higher education have sought to develop new curricula that enhance students’ abilities to tackle climate change locally and globally. Universities have developed virtual learning exchange curricula that connect students from multiple countries and prepare them to work collaboratively to develop solutions for local and global challenges such as climate change. This paper presents findings from a virtual exchange program in which undergraduate university students living in the Greater Chicago region in the United States and the city of Calabar in Nigeria researched and reported on experiences of climate change impacts within their local environments and appropriate ideas for mitigation and adaptation.